Simulasi Antrian: Suatu Tinjauan Konsep Pustaka - Hendy Tannady (Universitas Bunda Mulia, 2017)
Queuing is an inevitable event in our daily life, such as payment at cashier, traffic jam, etc. Queue appears because the necessity of service that exceeds service capacity or the available servers, so arrived customers cannot be served immediately. Some solution can be implemented to solve the problems. One of the solutions is by adding the service facilities can be given to minimize queue or to prevent queue. But, by adding the service facilities, will minimized the profit until accepted levels. On the contrary, the long delay of queue will cause the loss of customers. This paper discusses about how to estimate the right solution to prevent queue without adding many service facilities and reach optimal condition of service.Keywords: Queue, Customers, Service Facilities